2014
DOI: 10.5194/acp-14-7431-2014
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon concentrations and sources in the marine boundary layer of the tropical Atlantic Ocean using four methodologies

Abstract: Combustion-derived aerosols in the marine boundary layer have been poorly studied, especially in remote environments such as the open Atlantic Ocean. The tropical Atlantic has the potential to contain a high concentration of aerosols, such as black carbon, due to the African emission plume of biomass and agricultural burning products. Atmospheric particulate matter samples across the tropical Atlantic boundary layer were collected in the summer of 2010 during the southern hemispheric dry season when open fire … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Further, the impact of BC aerosols on the snowpack, surface radiation, and temperature changes over the HKH region based on simulations in global climate models suggest a considerable impact of anthropogenic forcing over the HKH region as compared to that over the Tibetan Plateau. However, the ability of coarse-gridded models to adequately simulate the snow depth and thereby the BC concentration in snow and atmospheric BC radiative forcing is limited (Menon et al, 2010;Ménégoz et al, 2014;Qian et al, 2015).…”
mentioning
confidence: 99%
“…Further, the impact of BC aerosols on the snowpack, surface radiation, and temperature changes over the HKH region based on simulations in global climate models suggest a considerable impact of anthropogenic forcing over the HKH region as compared to that over the Tibetan Plateau. However, the ability of coarse-gridded models to adequately simulate the snow depth and thereby the BC concentration in snow and atmospheric BC radiative forcing is limited (Menon et al, 2010;Ménégoz et al, 2014;Qian et al, 2015).…”
mentioning
confidence: 99%
“…studies (e.g., Qian et al, 2015;Ménégoz et al, 2014;Matt et al, 2018). It is also, therefore, necessary to carry out a more detailed validation of model estimates for BC aerosols along with the meteorology with a widely distributed observations across the HKH sites.…”
Section: Sensitivity Analysis Of the Annual Glacier Runoff-albedo Relmentioning
confidence: 99%
“…It is observed that while BC concentration and BC-AOD due to emissions from the IGP has a slightly higher value during pre-monsoon than winter, it is vice-versa for that due to emissions from AFWA. This feature is inferred likely due to emissions of biomass burning (crop-waste and forest fires) which is more prominent during pre-monsoon over the IGP but that during winter over AFWA as obtained from the information of firecounts data from satellite-based measurements (Pohl et al, 2014;Verma et al, 2014).…”
Section: Sensitivity Analysis Of the Annual Glacier Runoff-albedo Relmentioning
confidence: 99%